A Novel Polymerase Chain Reaction (PCR)-Based Method for the Rapid Identification of Chrysodeixis includens and Rachiplusia nu - Guilherme A. Gotardi; Natália R. F. Batista; Tamylin Kaori Ishizuka; Luiz H. Marques; Mário H. Dal Pogetto; Amit Sethi; Mark L. Dahmer; Timothy Nowatzki (Insects)
Chrysodeixis includens and Rachiplusia nu are two species belonging to the Plusiinae subfamily within the Noctuidae family. Due to their morphological similarity, the identification of their larvae is difficult and time-consuming. A rapid and accurate identification of these two species is essential for their management as these species exhibit differential susceptibilities to insecticides and crops engineered to express Bacillus thuringiensis (Bt) proteins, and a molecular tool can easily provide this differentiation. Currently, molecular analysis can identify these species through genetic sequencing, an expensive and time-consuming process. In our study, after sequencing part of the mtDNA cytochrome c oxidase I (COI) gene and based on the differences found in the gene of each species, a set of species-specific primers was developed: one reverse primer common to both species and two forward primers, specific to each species, amplifying fragments of 199 base pairs (bp) for C. includens and 299 bp for R. nu. Our results indicate that the primers were specific for these species, enabling the identification of individuals directly through agarose gel. The new methodology proved to be accurate, rapid, and reliable for the correct identification of these two species of loopers.